Parvovirus B19 infection in sickle cell disease: An analysis from the Centers for Disease Control haemoglobinopathy blood surveillance project. Issue 3 (4th March 2020) - Majumdar, Suvankar; Bean, Christopher J.; De Staercke, Christine; Bost, James; Nickel, Robert; Coates, Thomas; Campbell, Andrew; Thompson, Alexis
Summary: Objective: In the multicentre Haemoglobinopathy Blood Surveillance Project, to evaluate the seroprevalence of parvovirus B19 and DNA viral load in sickle cell disease (SCD). Background: Although the epidemiology of parvovirus B19 seropositivity in SCD has been well documented, there are few studies that have assessed possible persistent parvovirus DNAemia and associated risk factors including blood transfusion. Methods: A qualitative analysis of parvovirus B19 serology using ELISA and quantitative parvovirus B19 DNA by RT‐PCR was performed in patients with SCD. Results: Of 322 patients, 113 (35%) were parvovirus IgG positive and 119 (37%) were IgM positive at enrolment. The prevalence of IgG positivity increased with age. 71/322 (22%) were parvovirus DNA positive at enrolment with a mean viral load of 15 227 ± 55 227 SD. (range 72‐329 238 IU/mL). Patients who were positive for parvovirus B19 DNA received a significantly higher red blood cell transfusion volume in the prior year compared to patients who were negative (mean RBC volume = 8310 mL vs 5435 mL, respectively; P = .0073). Seventy‐seven patients had follow‐up testing approximately 1 year after enrolment and 11/28 (39%) patients had persistently positive IgM. Conclusion: Further studies are needed to better understand the natural history of parvovirus B19 infection in SCD especially in relation to RBC transfusion as a risk factor, as well as disease outcome and severity.